Handbook of industrial membrane technology - Porter, Mark C. (Noyes Publications, 1990)
This handbook emphasizes the use of sythetic membranes for separations involving industrial or municipal process streams. Discussions on theory, engineering aspects, membrane preparation, and typical and projected applications of the various membrane processes are included.
Keywords: Membranes (Technology) -- Handbooks, manuals, etc.; elektronické knihy; electronic books